Sorcery and the dividual in Australia. (25th July 2016) - Smith, Benjamin R.
Abstract : In this article I present an analysis of Australian Aboriginal sorcery, applying concepts from the New Melanesian Ethnography. My starting‐point is Keen's approach to magic among the Yolngu, which engages Strathern's concept of the dividual, but which focuses on the extension of partible aspects of the person in space and time. Building on Keen's analysis, I draw on ethnographic material from Cape York Peninsula to argue that Aboriginal sorcery might be understood not only as the extension of partible aspects of the person, but also in terms of the interplay between the internal divisions and external connections of dividual personhood, linking that interplay to the various invasive techniques understood to be employed by sorcerers. On that basis, I argue that, in the central Peninsula, sorcery beliefs are best understood as forms of 'indigenous analysis' (Strathern) or 'naïve critique' (Kapferer) that simultaneously articulate and obscure the anxieties that inhere in postcolonial Aboriginal sociality.